Urgensi Pola Asuh Orang Tua untuk Menghindari Perilaku Bermasalah Remaja - Nurul Alifah; Dea Kartika Utami; Adinda Dwi Cahyani; Ully Arta Silitonga; Rizki Novirson; Resti Okta Sari (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Adolescence is a transitional period prone to problematic behavior due to significant physical, emotional, and social changes. One of the main factors influencing adolescent behavior is parenting style. This study aims to examine the importance of parenting styles in preventing problematic behavior in adolescents. The method used in this study is a literature review. The results of the study indicate that democratic (authoritative) parenting plays a protective role in preventing delinquency, aggressive behavior, and maladaptive behavior. Conversely, authoritarian and permissive parenting styles tend to be positively correlated with increased deviant, aggressive, and antisocial behavior in adolescents. Furthermore, self-control and morality act as mediators that can strengthen or reduce the influence of parenting styles on juvenile delinquency. Thus, the role of the family as the primary and primary environment is crucial in early detection and prevention of problematic behavior in adolescents.